4 Dekade Kampanye Diaspora Papua pro Kemerdekaan Papua di Kawasan Pasifik - Siagian, Muhnizar (Universitas Cenderawasih, 2025)
This study examines four decades of Papuan diaspora efforts to campaign for Papuan independence in the Pacific region. It analyzes campaigns beginning in the 1980s with figures such as John Otto Ondawame and Andy Ayamiseba, later continued by leaders like Benny Wenda. Through a historical approach, the research investigates how these pro-independence campaigns spotlight the controversial cession of Papua to Indonesia in 1969, subsequent political violence, human rights violations, and the role of Melanesian solidarity. The study argues that the Papuan diaspora has been instrumental in internationalizing the Papuan issue and rallying support from a wide range of actors, including state officials, traditional leaders, and civil society groups. Findings reveal that, despite inconsistent backing from state actors, the sustained diaspora campaign has significantly raised regional and global awareness of Papuan independence. This research fills a gap in literature by highlighting the impact of diaspora activism on the Papuan independence process. KEYWORDS Melanesian Solidarity; Papuan Diaspora; Papuan Issue; Pacific Region